Alemtuzumab-based therapy for Secondary Malignant Histiocytosis arising from Pre-B-ALL. (2018) - Abid, Muhammad Bilal; Wadhera, Karan; Bird, Jenny M.; Pawade, Joya; Marks, David I.
Abstract : Clinical Practice Points: Secondary Malignant Histiocytosis (SMH) is an exceedingly rare, life-threatening condition that invariably occurs in the presence of an underlying monoclonal hematologic disorder. Prognosis of SMH remains dismal and there is no established treatment. We report a case of a patient who developed SMH during induction chemotherapy for his underlying pre-B-ALL, that caused persistently high fevers and was only diagnosed by a marrow while cytopenic in phase 2 induction. He was treated with alemtuzumab-based therapy that reduced the histiocytic infiltration of the bone marrow from 80% to 15% and made him eligible to undergo T-cell replete allogeneic stem transplantation from his sibling. This report is the first to highlight the role of alemtuzumab, an anti-CD52 monoclonal antibody, in clonal disorders originating from transdifferentiation. The alemtuzumab-based regimen should be reserved only for carefully selected allogeneic transplant patients.